Penanaman Ajaran Agama Hindu Berbasis Budaya dalam Membentuk Karakter Peserta Didik - Made Mardika (UHN IGB Sugriwa Denpasar, 2015)
The rapid development of science and technology these days have influenced the characters of the children, who are faced with heavy challenges. Teaching children should be then directed towardsÂ strenghtening their morals. Regarding that, it needs a neotraditional norm that is based on the traditional origins. The Hindu education could become the normative agent that builds any modern Indonesian characters through their local wisdoms that are motivative to the children. On the instrumental level, the primary values to be taught are autonomy, dignity, creativity, morality, pride, and sense of aesthetics, and democracy awareness. They should preserve the local cultural heritage, including the languages and the arts, while adapting the global trend. As the educators, the teachers at schools as well as the parents at homes must be the role models whose responsibilities and disciplines are followed.